A Highly Thermostable Xylanase from Stenotrophomonas maltophilia: Purification and Partial Characterization. (14th December 2013) - Raj, Abhay; Kumar, Sharad; Singh, Sudheer Kumar
Abstract : Seven xylanolytic bacterial strains were isolated from saw-dust dump soil. The bacterial strain X6 was selected on the basis of the highest xylanase activity with no cellulase contamination. It was identified as Stenotrophomonas maltophilia by biochemical tests and 16S rRNA gene sequencing approach. Xylanase production studies by S. maltophilia on different commercial xylans and agro-industrial residues suggested that wheat bran was the best carbon source for xylanase production (26.4 ± 0.6 IU/mL). The studies with inorganic and organic nitrogen sources suggested yeast extract as the best support for xylanase production (25 ± 0.6 IU/mL). Maximum xylanase production was observed at initial medium pH = 8.0 (23.8 ± 0.4 IU/mL) with production at pH = 7.0 and pH = 9.0 being almost comparable. Xylanase produced by S. maltophilia was purified to homogeneity using ammonium sulfate precipitation, gel filtration, and ion exchange chromatography. The final purification was 5.43-fold with recovery of 19.18%. The molecular weight of the purified xylanase protein was 142 kDa. Both crude and purified xylanase had good stability at pH = 9.0 and 80°C with activity retention greater than 90% after 30 min incubation. The enzyme stability at high temperature and alkaline pH make it potentially effective for industrial applications.